Classes of drinking motives among American Indian youth drinkers - Davis, Samuel R. (Psychol Addict Behav, 2019)
Research exploring American Indian (AI) youth drinking motives and their relation to negative outcomes is critical due to higher rates of alcohol use and early exposure to intoxication in the population. The purpose of this study is to explore classes of drinking motives as they relate to heavy episodic drinking, perceived discrimination, religious importance, ethnic identity, and ethnic pride. This study is part of an ongoing epidemiologic and etiologic investigation of substance use among AI youth drinkers living on or near reservations (N = 1,934, M(age) = 15.31). A Latent Class analysis (LCA) was conducted to discern latent classes of drinking motives. Once latent classes were identified, differences in perceived discrimination, ethnic pride, ethnic identity, spirituality, and heavy episodic drinking were tested. A two-class solution provided the best overall model fit to the data. The higher coping and enhancement motive class was associated with significantly greater heavy episodic drinking, perceived discrimination, and ethnic identity compared to the low motive class. Further, the class structure did not differ between 7(th) and 8(th) graders and 9(th) – 12(th) graders. Results indicate that among AI youth, the class with strong motives to drink for coping or enhancement had higher ethnic identity, greater risk of heavy episodic drinking, and greater perceived discrimination compared to the class with low motives. Future research should examine additional factors and stressors that may be associated with these classes of drinking motives and are unique to the AI population.